Critical literature review: preparation strategies - Syed Hassan, Syed Tajuddin; Mohd Elias, Saliza; Mehrdad, Jalalian (Knowledge Kingdom Publishing, 2017)
The imperative needs for, and characteristics of an effective critical literature review, provide the foreground baseline deliberation. A visual model depicting synthesized major modular components of a research project delineate impact points of literature review inputs. The three major modules represent preparation, data capture, and data rendering-analysis-interpretation phases of research. Within each module, the literature review elements to be incorporated are elaborated. Steps and optimal articulation-action strategies are highlighted and embedded with examples from literature and theses. Development of competency and efficacy in critiquing and evaluating, which comprised mandatory skills to acquire, is especially focussed.